Kondisi ekonomi dan dukungan keluarga sebagai faktor risiko putus sekolah: Kondisi ekonomi dan dukungan keluarga sebagai faktor risiko putus sekolah - lia lia; Martin Tinaida; Sukriadi Hasibuan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2026)
School dropout at the primary level is not a single event but a gradual process marked by recurrent absence, declining learning motivation, incomplete assignments, and limited access to educational needs. This study aims to describe how family economic conditions and family support shape the risk of primary school dropout and to identify preventive actions involving families and schools. A descriptive qualitative approach was employed. Data were collected through observation, semi-structured interviews, and document analysis, then analyzed through coding, categorization, thematic presentation, and conclusion drawing. Source and technique triangulation were used to strengthen credibility. The findings indicate that unstable family income constrains the provision of uniforms, stationery, transportation, and other learning needs while also reducing children's study time when they are required to assist family work. Family support functions as a protective factor through emotional encouragement, attendance monitoring, study routines, appreciation of effort, and communication with teachers. Strong support does not remove economic hardship, but it can reduce its negative effect on students' engagement and persistence. Early intervention should therefore combine targeted educational assistance, systematic attendance monitoring, parent-teacher communication, and family education.